Efektivitas E-mail Mobile dalam Kegiatan Administrasi dan Pengarsipan pada Dinas Pendidikan Kota Surabaya - Romadhon, Mohammad Ulil Albab Nur; Hertati, Diana (VISA: Journal of Vision and Ideas, 2025)
In the modern era, information and communication technology is very important for society. In the modern era, information technology plays a very important role, especially in terms of public services, with the development of communication and information tools, there will be many electronic systems that can make it easier for public servants to carry out services to the community. In addition to the administrative interests of government or offices, the development of technology and information functions in terms of archiving, documentation, and correspondence in a government or office environment will become more effective. Therefore, the use of E-mail Mobile plays a very important role in carrying out administrative activities, archiving, documentation, and correspondence within the scope of government agencies and offices. The Surabaya City Education Office has used the mobile e-mail system to carry out administrative and archiving activities, so that it will be effective in providing services and storing archives.